2019
DOI: 10.1016/j.canlet.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived cell line models revealed therapeutic targets and molecular mechanisms underlying disease progression of high grade serous ovarian cancer

Abstract: Patient-derived cell line models revealed therapeutic targets and molecular mechanisms underlying disease progression of high grade serous ovarian cancer', Cancer letters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…For example, in multistep cell models of 34 cancer cell lines derived from 23 HGSOC patients to develop new treatments for therapy, it is demonstrated that loss of TP53 wild type is the main driving force of tumorigenesis and tumor progression in HGSOC. [ 156 ] Cancer cell line models can be applied for clinical therapeutic targets in multistep tumor progression. Over the last decade, to develop groundbreaking therapeutic agents and recapitulate cell heterogeneity in vivo, in many tumor types, such as oral cancer, [ 157 ] breast cancer, [ 158 ] colorectal cancer, [ 159 ] prostate cancer, [ 160 ] pancreatic cancer, [ 161 ] and more recently, ovarian cancer, [ 162 ] 3D primary cell models in vitro have made stride forward in building tumor organoids ( Figure ), a type of precise oncology remodeling, which at largest extent recapitulates the tumorigenesis in vivo.…”
Section: Instructive Cell Constructs In Tissue Engineering and Precismentioning
confidence: 99%
“…For example, in multistep cell models of 34 cancer cell lines derived from 23 HGSOC patients to develop new treatments for therapy, it is demonstrated that loss of TP53 wild type is the main driving force of tumorigenesis and tumor progression in HGSOC. [ 156 ] Cancer cell line models can be applied for clinical therapeutic targets in multistep tumor progression. Over the last decade, to develop groundbreaking therapeutic agents and recapitulate cell heterogeneity in vivo, in many tumor types, such as oral cancer, [ 157 ] breast cancer, [ 158 ] colorectal cancer, [ 159 ] prostate cancer, [ 160 ] pancreatic cancer, [ 161 ] and more recently, ovarian cancer, [ 162 ] 3D primary cell models in vitro have made stride forward in building tumor organoids ( Figure ), a type of precise oncology remodeling, which at largest extent recapitulates the tumorigenesis in vivo.…”
Section: Instructive Cell Constructs In Tissue Engineering and Precismentioning
confidence: 99%
“…Serous ovarian cancer (SOC) is the main type of ovarian cancer, which progresses quickly, lacks effective treatment and is prone to bladder metastasis ( 6 ). At present, surgery supplemented by chemotherapy remains the main treatment option for advanced stages of SOC, and treatment outcomes are unsatisfactory ( 7 ). In recent years, targeted therapy has shown advantages for SOC treatment ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of additional proliferation in the presence of hormone precursors is most likely a consequence of the fact that all cell lines already reached their respective maximum proliferation capacity from the stimulatory effect of various cyclines (e.g., D1, E1, A1, and B) overexpressed in these cell lines. Genes such as CDKN1A BAX or TIGAR, controlling apoptosis and cell cycle arrest, are furthermore downregulated [26,49]. These data indicate that the loss of wild type p53 function is the major driving force of tumor cell progression [50].…”
Section: Discussionmentioning
confidence: 94%
“…Expression of selected genes (CYP3A4, CYP19A1, TP53, PAX8, AR, ESR1, ESR2, PGR, IL6, EGFR, ERBB2, and ESRRG) in the HGSOC cell lines 13363, 13699, 13914_1, and 15233 was analyzed by next-generation sequencing, as described previously [49]. Expression data for these selected genes in Kuramochi and OVSAHO cells were taken from the GENEVESTIGATOR platform [56].…”
Section: Gene Expression Analyses and Identification Of Gene Mutationsmentioning
confidence: 99%
See 1 more Smart Citation